2021
DOI: 10.1007/s11606-021-07107-7
|View full text |Cite
|
Sign up to set email alerts
|

Statin Use in Older Adults for Primary Cardiovascular Disease Prevention Across a Spectrum of Cardiovascular Risk

Abstract: BACKGROUND: There remains uncertainty regarding optimal primary atherosclerotic cardiovascular disease (ASCVD) prevention practices for older adults. OBJECTIVE: To assess statin treatment patterns and incident ASCVD among older patients for primary prevention across the spectrum of ASCVD risk. DESIGN: Retrospective cohort study of participants without ASCVD aged 65-79 years. Patients were stratified by age (65-69, 70-75, > 75 years) and 10-year ASCVD risk category (low/borderline, intermediate, high) based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Our study extends prior work by Sarraju et al, evaluated statin use for primary prevention in individuals 65–79 years of age and showed that older adults >75 years were less likely to receive a moderate or high intensity statin regardless of ASCVD risk compared to those who were <75 years [16] . Similar to our result these patients had a higher incidence of ASCVD events – followed up to only 1 year.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our study extends prior work by Sarraju et al, evaluated statin use for primary prevention in individuals 65–79 years of age and showed that older adults >75 years were less likely to receive a moderate or high intensity statin regardless of ASCVD risk compared to those who were <75 years [16] . Similar to our result these patients had a higher incidence of ASCVD events – followed up to only 1 year.…”
Section: Discussionsupporting
confidence: 86%
“…This is further evidence that statin utilization in older adults is a missed opportunity that has potential for improvement. Currently there is limited comparative data on statin initiation in older adults however, trends of the limited data support that it is possible that the rates are low as we have shown given various practice model sites across the healthcare system [16] .…”
Section: Discussionmentioning
confidence: 84%
“…Thus, the PCE calculation approach does not allow for a nuanced risk assessment of older adults, for whom an individualized consideration of comorbid conditions, frailty, and reduced life expectancy is paramount. Uncertainty in risk assessment often leads to fewer prescriptions for statin therapy in adults >75 years of age, likely causing some to be deprived of potentially marked benefits [72].…”
Section: Ascvd Risk Assessment In Older Adultsmentioning
confidence: 99%